Finance and Development, June 1972. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1972)
This paper describes the IMF's activities in developing countries. The paper highlights that there are several instances in which the Articles of Agreement require a member to consult on its policies with the IMF. Other actions by a member concerning the exchange rate of its currency, or its exchange regime generally require the IMF's prior approval or concurrence. Under the IMF's policy, a member also discusses with the IMF changes in its financial programs in support of which the use of the IMF's resources has been pledged.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet